PRODUKTIVITAS KINERJA DEWAN PERWAKILAN RAKYAT DAERAH KOTA KUPANG DALAM MELAKSANAKAN FUNGSI PENGAWASAN DI KOTA KUPANG - Salsa Dianprima Tonubessi; Saryono Yohanes; Hernimus Ratu Udju (Petitum Law Journal, 2026)
Since 2020 until now, the world, including the City of Kupang, has been hit by the spread of corona virus disease 2019 which does not yet appear to be over and requires enormous attention and budget to carry out efforts to overcome it. The research in this thesis discusses the productivity of the supervisory performance of the Kupang City Regional People's Representative Assembly in dealing with corona virus disease 2019 in Kupang City.The method used by the author is a normative juridical research method using a case methodology. The findings of this research suggest that the Kupang City Regional Representative Council in carrying out its supervisory function, including in handling corona virus disease 2019 in Kupang City, continues to use its authority and function normatively, by tightening oversight so that all corona virus disease 2019 countermeasures policies in Kupang City can run as they should and can more effective in controlling the spread of corona virus disease 2019 in Kupang City.